High‐intensity breastfeeding improves insulin sensitivity during early post‐partum period in obese women with gestational diabetes - Yasuhi, Ichiro; Yamashita, Hiroshi; Maeda, Kazuhisa; Nomiyama, Makoto; Mizunoe, Tomoya; Tada, Katsuhiko; Yorozu, Moe; Ogawa, Masanobu; Kodama, Takashi; Yamaguchi, Ken; Okura, Naofumi; Kawakami, Kosuke; et al. (Diabetes/metabolism research and reviews, 2019)
Aim To investigate whether high‐intensity breastfeeding (HIB) reduces insulin resistance during early post‐partum period in women with gestational diabetes (GDM), independent of post‐partum weight change (PWC). Materials and methods In this multicentre prospective study, we included Japanese women with GDM who underwent a 75‐g oral glucose tolerance test (OGTT) during early post‐partum. We measured plasma insulin during OGTT to obtain a homeostasis model of assessment of insulin resistance (HOMA‐IR). We defined the condition in which infants were fed by breastfeeding alone or greater than or equal to 80% of the volume as HIB, and other statuses, including partial and nonbreastfeeding, as non‐HIB. We investigated the association between post‐partum HOMA‐IR and the breastfeeding status after adjusting for confounders including PWC. Results Among 222 women with GDM who underwent the OGTT at 7.9 ± 2.3 weeks post‐partum with a PWC of −7.8 ± 3.4 kg, although the rate of abnormal glucose tolerance (prediabetes and diabetes) did not differ between the groups (33% vs 32%), the HOMA‐IR in the HIB women (n = 166) was significantly lower than that in the non‐HIB women (n = 56) (1.12 ± 0.85 vs 1.72 ± 1.43, P = 0.0002). The effect of the HIB was independently associated with lower HOMA‐IR after adjusting for confounders including PMC. However, the subgroup analysis according to their pre‐pregnancy obesity states showed that the effect was seen only in the obese subjects (BMI ≥ 25). Conclusions In obese Japanese women with GDM, HIB has a significant effect in reducing insulin resistance during early post‐partum, independent of the post‐partum weight loss.